PENGARUH DOSIS BOKASHI TERHADAP PERTUMBUHAN DAN PRODUKSI PADA PEMOTONGAN PERTAMA RUMPUT GAJAH MINI (Pennisetum Purpureum cv. Mott) - Azaria Dhea Gantina; Farida Fathul; Liman Liman; Muhtarudin Muhtarudin (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This research aims was to determine the effect of bokashi dose on plant height, number of tillers, percentage of stems, fresh production, and dry matter production and also to determine the optimum dose of bokashi to obtain the best results on growth and production at the first harvest of dwarf elephant grass. This research was conducted in March 2020 - July 2020 in Sidodadi Asri village, Jati Agung district, South Lampung regency. This research used a Completely Randomized Design (CRD) with 4 levels of treatment, namely P0 (control); P1 (bokashi dosage 30 tons/ha); P2 (bokashi dosage 40 tons/ha); and P3 (bokashi dosage 50 tons/ha). Each experimental treatment unit has plot measuring 2x2 m2. Each trial unit was repeated 3 times, so there were 12 trial units. The data were analyzed by variations analyzed at 5% and or 1% level, after that it was followed by orthogonal polynomial test. The results showed that the dose of bokashi had a significant effect (P<0,05) on plant height, fresh production, and dry production, but had no significant effect (P>0,05) on number of tillers, and percentage of stems. The effect of bokashi fertilizer on plant height was obtained by using the optimum bokashi dose of 36.73 tons/ha and the equation was = 60,13 + 35,38x - 6.62x2 [0 ; 50 ton/Ha] (P<0,01). The optimum dose was not obtained for the number of tillers, percentage of stems, fresh production, and dry production. Keywords: Plant height, Number of tillers, Percentage of stems, Fresh production, Dry production